Populists in power: Economic and political consequences - Manuel Funke; Moritz Schularick; Christoph Trebesch (EconPol Forum, 2024)
Populism at the government level is on the rise and we are living in a populist era. Populist leaders cling to power and populism often returns to countries. Populist governments are a drag on economic growth. Economic nationalism and protectionism are a common feature of populists in power. Populist leaders typically undermine democratic institutions.
Keywords: 330